2015
DOI: 10.1155/2015/464161
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter Wave Treatment Inhibits Apoptosis of Chondrocytes via Regulation Dynamic Equilibrium of Intracellular Free Ca2+

Abstract: The molecular mechanisms of TNF-α-induced apoptosis of chondrocyte and the role of Ca2+ mediating the effects of MW on TNF-α-induced apoptosis of chondrocytes remained unclear. In this study, we investigated the molecular mechanism underlying inhibiting TNF-α-induced chondrocytes apoptosis of MW. MTT assay, DAPI, and flow cytometry demonstrated that MW significantly increased cell activity and inhibited chromatin condensation accompanying the loss of plasma membrane asymmetry and the collapse of mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The present study results consistent with previous studies which showed that TNF-α induced chondrocyte apoptosis via upregulated expression level of ROS and NO. In addition, previous studies, as well as the current study, have demonstrated that TNF-α induced the pro-apoptotic protein Bax production and reduced the anti-apoptotic protein Bcl-2 production, leading to hypercatabolism in chondrocytes ( Ye et al, 2015 ). It should be noted that there are other proinflammatory cytokines contribute to the autophagy suppression and apoptosis induction in OA ( Goldring and Otero, 2011 ).…”
Section: Discussionsupporting
confidence: 67%
“…The present study results consistent with previous studies which showed that TNF-α induced chondrocyte apoptosis via upregulated expression level of ROS and NO. In addition, previous studies, as well as the current study, have demonstrated that TNF-α induced the pro-apoptotic protein Bax production and reduced the anti-apoptotic protein Bcl-2 production, leading to hypercatabolism in chondrocytes ( Ye et al, 2015 ). It should be noted that there are other proinflammatory cytokines contribute to the autophagy suppression and apoptosis induction in OA ( Goldring and Otero, 2011 ).…”
Section: Discussionsupporting
confidence: 67%
“…Considering that chondrocytes are responsible for secreting extracellular matrix, and the maintenance of cartilage homeostasis is involved in the pathological characteristics of OA, promoting chondrocyte proliferation may be a prospective and potential method for the treatment of OA (1921). …”
Section: Discussionmentioning
confidence: 99%
“…The incidence of osteoarthritis (OA) still poses a major public health challenge throughout the world, and, currently there is no thoroughly effective therapy available. Considering that chondrocytes are responsible for secreting extracellular matrix, and the maintenance of cartilage homeostasis is involved in the pathological characteristics of OA, promoting chondrocyte proliferation may be a prospective and potential method for the treatment of OA ( 19 21 ).…”
Section: Discussionmentioning
confidence: 99%